Do fish remains provide reliable palaeoenvironmental records? An examination of the effects of cooking on the morphology and chemistry of fish otoliths, vertebrae and scales. (October 2016) - Disspain, Morgan C.F.; Ulm, Sean; Izzo, Christopher; Gillanders, Bronwyn M.
Abstract: The morphological and chemical properties of fish calcified structures provide excellent environmental and anthropogenic proxies; however, pre-depositional handling may alter these properties, confounding interpretations. This study examines the effects of some traditional processing and cooking methods on the morphological and chemical properties of modern fish otoliths (ear bones), vertebrae, and scales using an experimental approach. Whole mulloway ( Argyrosomus japonicus ) were treated using a range of techniques, including boiled in freshwater and saltwater; roasted directly on a fire and wrapped in clay; salted; and completely burnt. Samples were also obtained from untreated fish as controls for comparison. Otoliths, vertebrae and scales from the samples were subjected to morphological, trace element ( 7 Li, 23 Na, 24 Mg, 55 Mn, 86 Sr, 138 Ba, 208 Pb, and 65 Zn all ratioed to 43 Ca) and stable isotope analyses (otoliths and vertebrae – inorganic δ 13 C and δ 18 O; scales – organic δ 13 C and δ 15 N). Results reveal disparities in the chemistry and morphology of otoliths and vertebrae processed in different ways. The otolith and vertebrae carbonate δ 18 O values were lower in samples that experienced heating; burnt samples differed significantly from the control samples. Otolith and vertebrae trace elements were largely unaffected by the treatments relative to the controls; however, some individual elements within the burning and salting groups varied significantly. The impacts observed in the fish scales were less substantial. Results provide a basis for evaluating the suitability of archaeological samples for analysis. We recommend avoiding the use of heated samples. Findings highlight the need to conduct palaeoenvironmental reconstructions based on chemistry and stable isotope data of archaeological remains with caution. Highlights: Otolith and vertebrae carbonate δ 18 O values were lower in samples heated during cooking. Otolith and vertebrae trace elements were largely unaffected relative to the controls. Stable isotope analysis of fish scales indicated that no significant alteration was observed. Palaeoenvironmental reconstructions using heated remains should be conducted with caution.